The Stages and levels of development of lexical competence in future English language teachers - Jalilov Olimjon Mukhidinovich (Zien Journals, 2022)
In this article, the stages of development of lexical competence in future English language teachers and levels in the concept of lexicon are understood as a collection of words of a certain linguistic richness, as well as words similar to them in terms of the function of combining lexical units, the lexical unit is considered as the primary source of lexical competence and in this regard, the effectiveness and impact of the work performed in the process of applying the qualification was discussed
Keywords: English language; lexical competence; qualification